WORKPLACE BULLYING: THE EXPERIENCE OF TEACHERS IN KUWADZANA CLUSTER, HARARE, ZIMBABWE - Awoniyi Samuel Adebayo; Ndlovu Juliet (European Scientific Journal, ESJ, 2014)
Bullying among teachers merited interest for many reasons. These included its possible detrimental effects on the students, its ability to cause low morale among teachers, a high turnover of trained staff and, poor quality of pupils’ results. This study examined the experience of workplace bullying among teachers in Kuwadzana Cluster, Harare, Zimbabwe. The experiences included verbal workplace bullying, nonverbal workplace bullying, practical workplace bullying and performance related workplace bullying. The survey research design was used for the study. The population for the study was five hundred and twenty six (526) teachers from Kuwadzana Cluster. The sample for the study comprised of one hundred and eighty (180) teachers from both primary and secondary schools. The research instrument for the study was a questionnaire of the five point Likert scale. The questionnaire was face and content validated and reliability was determined using the Cronbach’s Alpha Reliability method. A reliability coefficient of 0.951 was obtained for the instrument. The data collected was analysed using the Statistical Package for Social Sciences (SPSS). The descriptive statistics and regression analysis was used for the analysis of data. The study revealed that teachers were sometimes subjected to belittling remarks about their work or personal life with a mean of 2.5698. On the overall, teachers in Kuwadzana cluster rarely experienced verbal workplace bullying, nonverbal workplace bullying, practical workplace bullying and performance related workplace bullying. Teachers rarely experienced stress and stress related health problems and mental health problems. They, however, experienced low morale as a result of workplace bullying with a mean value of 2.8111.The more qualified the teachers; the more they experienced workplace bullying as indicated by the positive Beta value of 0.623. The experience of workplace bullying accounted for 49.7% variance and had a high effect on the effects of workplace bullying. Based on these findings, recommendations were made